KEBIJAKAN HARI SANTRI NASIONAL DAN INOVASI KEBIJAKAN PENDIDIKAN ISLAM - Kholilur Rahman (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
This paper reviewed literature about the background of the policy on Hari Santri Nasional (HSN). Historical and political approach emphasis on historical data as well as political factors that affect its, were sought to acquire a comprehensive understanding. This study described the presidential decree about the HSN was based on the implementation of the normative values of justice in Islam political. The policy response of HSN as an integral part of public policy innovation is the moment of awakening "kaum sarungan ", especially when their education is exposed to the impact of globalization. Innovation of public policy conceptually viewed as a change of viewpoints over the existing problems so as to bring up the solution. The scope of conceptual innovation are emergence paradigm, ideas, thoughts and new breakthroughs that were previously unimaginable.